EU-wide income inequality in the era of the Great Recession - Péter Benczúr; Zsombor Cseres-Gergely; Péter Harasztosi (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2017)
This paper uses microdata to look at stylised facts of EU-wide income inequality during the 2006-2013 period. Our contribution is to bring together four elements of the analysis that has appeared only in separation so far. Our analysis is EU-wide, but regionally detailed, looks at the longeset possible term with harmonized survey data, uses inequality indicators sensitive to different parts of the income distribution and shows the contribution of income components to income inequality. Using this, we are able to show how the dynamics of inequality in Europe was shaped by changes on the periphery, in hours worked, in wages and in the structure of households.
Keywords: D31; E24; H31; J31; 330; income inequality; European Union